Influence of chromium citrate on oxidative stress in the tissues of muscle and kidney of rats with experimentally induced diabetes - О. О. Sushko; R. J. Iskra; L. I. Ponkalo (Regulatory Mechanisms in Biosystems, 2019)
Chromium is one of the important trace elements that is essential for carbohydrate, protein and lipid metabolism. Chromium improves glucose metabolism and reduces insulin resistance due to increased insulin sensitivity. Therefore, it is important to consider the use of chromium citrate as a nutritional supplement with potential hypoglycemic and hypolipidemic effects. In this research work, we investigated the activity of the antioxidant system and the level of lipid hydroperoxides in the tissues of skeletal muscles and kidneys of experimental diabetic rats and for rats which received in their daily diet chromium citrate in the amounts 0.1 and 0.2 μg/mL of water. We induced the experimental model of diabetes by intraperitoneal injection of alloxan in the amount 150 mg/kg of body weight of the animals. We monitored glucose levels by measuring daily glucose levels with a portable glucose meter. For research, we selected animals with a glucose level > 11.1 mmol/L. We monitored the body weight of rats. On the 40th day of the study, we withdrew the animals from the experiment by decapitation. We selected the tissue for research, namely skeletal muscles and kidneys. In samples of the tissue homogenates, we measured the activity of antioxidant enzymes and the content of lipid peroxide oxidation products. As a result of our research, we found that the products of lipid peroxide oxidation and glutathione peroxidase activity increased in skeletal muscle of animals with diabetes mellitus. The activity of glutathione reductase, catalase, superoxide dismutase, and the content of reduced glutathione decreased at the same time. In the kidneys of diabetic rats, the activity of glutathione peroxidase, glutathione reductase, catalase and content of lipid hydroperoxides increased but the activity of superoxide dismutase and the content of reduced glutathione decreased. The addition of chromium citrate to the diet of animals in amounts 0.1 and 0.2 μg/mL led to the suppression of oxidative stress. The activity of catalase, glutathione peroxidase and the content of lipid hydroperoxides, TBA-positive substances decreased. Also, the activity of superoxide dismutase increased with the addition of chromium citrate. These results indicate normalization of antioxidant defense in the skeletal muscle and kidneys of experimental rats with experimental diabetes given chromium citrate in the amount 0.1 mg/mL of water.